PEMBAGIAN TUGAS APEL PAGI MINGGUAN PEGAWAI INSTANSI XYZ DENGAN MENGGUNAKAN PEWARNAAN GRAF BESERTA ANALISIS BEBAN PENUGASAN: Distribution Of Weekly Morning Call Assignments Of XYZ Agency Employees Using Graph Coloring And Assignment Load Analysis - Diana, Ulfa; Fauzi, Rifky (Yayasan Al-Amin Qalbu, 2025)
This study addresses the issue of the weekly morning roll call duty assignment at XYZ Agency. The allocation of morning roll call duties at XYZ Agency has been incidental, leading to uneven task assignments for employees. The author proposes a solution to this problem by implementing the Welch-Powell Algorithm on Graph Coloring to determine the allocation of morning roll call duties for XYZ Agency employees. This is achieved by representing each employee as a point, and the edges represent job similarities. The graph coloring results in this study produce 4 colors: red, green, blue, and purple, with connected points having different colors. The findings reveal that 20 employees participate in the roll call duty each month. The duty assignments are then made for six months and compiled into a task assignment table. Based on descriptive statistical results, each employee receives an average assignment of 4.68 times with a standard deviation of 1.38. Furthermore, the Levene's Test is employed to ensure the equality of workload among different employee job groups. The results indicate differences in the assignment workload among job groups